CONFIDENTIAL INTERACTION BETWEEN PASSENGERS AND CUSTOMS OFFICERS AT MAKASSAR SULTAN HASANUDDIN INTERNATIONAL AIRPORT - Irwansyah Djaya, Dennis; Alimuddin Unde, Andi; Maria Fatimah, Jeanny (Jurnal Konseling Pendidikan Islam, 2023)
In addition to their other duties as civil servants of the state, customs officers at Sultan Hasanuddin Makassar International Airport are tasked with safeguarding the local populace from the introduction of harmful foreign substances like drugs. According to the latest data from the National Narcotics Agency Survey, one in every 55 Indonesians (between the ages of 15 and 64) has a problem with substance use. One of the customs officers has made stopping the entry of illegal drugs into Indonesia his top priority after learning the truth about these substances. Passenger conduct can be detected through conversation with other passengers. The customs officer must learn about the passenger's background during the conversation to check for illegal items being smuggled. Uncertainty in interpersonal communication arises for customs personnel when they meet people entering Indonesia. The study's goal is to examine the methods used by customs agents to make passenger interactions more certain by reducing ambiguity. Descriptive qualitative research using the interactive model of Miles and Huberman was employed for this study's data collection and analysis. The research concluded that customs officers can lessen communication risks by gathering information about passengers through direct interpersonal communication with passengers and by asking a variety of questions that can describe the passenger profile, as well as through observation of passengers' verbal and nonverbal behavior.